2020
DOI: 10.3389/fimmu.2020.568362
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoregulatory Role of Myeloid-Derived Suppressor Cells in the Pathogenesis of Rheumatoid Arthritis

Abstract: Myeloid-derived suppressor cells (MDSCs) are a group of cells that regulate the immune response and exert immunosuppressive effects on various immune cells. Current studies indicate that MDSCs have both anti-inflammatory effects and proinflammatory effects on rheumatoid arthritis (RA) and RA animal models. MDSCs inhibit CD4 + T cells, which secrete proinflammatory factors such as IFN-γ, IL-2, IL-6, IL-17, and TNF-α, by inhibiting iNOS, ROS, and IFN-γ and promoting the production of the anti-inflammatory factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…It is well known that B cells are a vital part pertaining to human adaptive immunity, whereas these cells under RA become a possible factor in RA pathogenesis (40). Local synthesizing process for cytokine (e.g., IL-1a, IL-23, IL-12, IL-6, and TNF-a) under the induction from local autoreactive B cell was suggested to impact pathologyassociated RA cells, triggering bone injury, inflammation, and immune disorder (41,42). It is currently evidenced that CD4+ T helper cells impact the pathogenesis of RA largely via the secreting process for cytokine and chemokine.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that B cells are a vital part pertaining to human adaptive immunity, whereas these cells under RA become a possible factor in RA pathogenesis (40). Local synthesizing process for cytokine (e.g., IL-1a, IL-23, IL-12, IL-6, and TNF-a) under the induction from local autoreactive B cell was suggested to impact pathologyassociated RA cells, triggering bone injury, inflammation, and immune disorder (41,42). It is currently evidenced that CD4+ T helper cells impact the pathogenesis of RA largely via the secreting process for cytokine and chemokine.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, systemically decreased levels of IL6 and TNFa were also observed in peripheral blood (Figure S1). As altered IL17 and IL10 levels were observed, which are crucial in Th17 and Treg differentiation and Th17 and Treg were reported to play indispensable roles in RA (42)(43)(44), the abundance of CD4 +IL17+ and CD4+ CD25+FOXP3+ cells in mice inguinal lymph node was evaluated by flow cytometry. The ratio of Treg/Th17 has been used to characterize the severity of RA (45,46), and our results showed that GSK-J4 could downregulate the ratio of Treg/Th17 (Figure S2), further suggesting that inhibition of demethylase activity could be beneficial to CIA, at least in the experimental RA mice model.…”
Section: Gsk-j4 Reduces H3k27me3 Level and Cytokine Expression In Mac...mentioning
confidence: 99%
“…It is of further note that, in a particular context, Myeloid-Derived Suppressor Cells (MDSCs), may differentiate towards osteoclasts precursors, [44,45]. In breast cancer, as reported by Sawant et al, MDSCs localized at bone metastatic sites, differentiated towards osteoclasts and contributed to bone destruction.…”
Section: Discussionmentioning
confidence: 90%